2017
DOI: 10.5455/njppp.2017.7.0307117052017
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and clinical response of superoxidized solution versus povidone iodine in the management of lower limb ulcers

Abstract: Background: Lower limb ulcers are debilitating and associated with significant morbidity, loss of productivity and decreased the quality of life. Currently used antiseptics are cytotoxic, damage the granulation tissue and interfere in the wound healing process. Superoxidized solution is nontoxic and contains reactive oxygen species which have bactericidal and wound healing properties. Aims and Objective: To compare the microbiological response and clinical efficacy of superoxidized solution versus povidone iod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Mean age was 41.05±17.37. Sridhar et al in his study on diabetic wounds reported the mean age of patients to be 56.4±18.6 years with male predominance [7].…”
Section: Discussionmentioning
confidence: 95%
“…Mean age was 41.05±17.37. Sridhar et al in his study on diabetic wounds reported the mean age of patients to be 56.4±18.6 years with male predominance [7].…”
Section: Discussionmentioning
confidence: 95%